Analisis pencatatan dan penilaian persediaan pada indomaret di samarinda - wiwin andi kartika (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
Wiwin Andikartika, 2017. Analysis of Recording and Assessment of Inventory at Indomaret in Samarinda, under the guidance of Dr. H. Hamid Bone and Mrs. Ferry Diyanti.Indomaret as a trading company also faces problems related to merchandise inventory. In the implementation of business operations, there is often a difference one of them is the recording and assessment. The following comparison of recording and appraisal according to SAK ETAP Chapter 11 About Inventory with inventory recording and valuation by Indomaret Scouting in Samarinda: Recording Inventory by Indomaret Scouting Samarinda using perpetual method that is where every transaction acceptance or expenditure of goods recorded in the card stock and according to SAK ETAP Chapter 11 The inventory recording uses the perpetual method so it can be said to be appropriate, but Indomaret Scout Samarinda makes a mistake in recording the quantity of goods sold. Assessment of Indomaret Scout inventory of Samarinda in accordance with SAK ETAP Chapter 11 that is using FIFO method, but inconsistency company in using cost price method of inventoryThe purpose of this research is to analyze and know the inventory record and appraisal applied At Indomaret Samarinda, in accordance with Financial Accounting Standards Entity Without Public Accountability (SAK ETAP) Chapter 11.Based on the results of the analysis obtained that the valuation of inventory price conducted by Indomaret Scout in Samarinda not in accordance with Financial Accounting Standards (SAK) Chapter 11 on inventory. The mismatch can be seen on each type of inventory sampled in this study experiencing the difference, the difference is fluctuated as follows: Oil 2 Ltr has a difference of Rp271.000, Tropical refil 2000 ml experience difference of Rp10.500, Ax Deo Spr Dark T 150 experienced Rp54,100 difference, Bebelac 3 750 Gr had difference of Rp40.000 and Lactogen / Grow 3 750gr experienced difference of Rp4,518.The conclusion of this research is that inventory recordings conducted by Indomaret Scouts have been in accordance with the Financial Accounting Standards (SAK) ETAP Chapter 11 on inventory while inventory valuation is not fully appropriate because there is still a mistake in entering the number of goods and inconsistent in using inventory valuation method so there is still difference on the ending inventory by Indomaret Scouting according to the calculation under SAK ETAP Chapter 11 on inventory.